1983
DOI: 10.1002/path.1711410404
|View full text |Cite
|
Sign up to set email alerts
|

Mesangiocapillary glomerulonephritis: A long‐term study of 40 cases

Abstract: Forty cases of mesangiocapillary glomerulonephritis are reviewed for whom both light and electron microscopy and full clinical data were available. Immunofluorescence microscopy (IF) was performed on 23 cases and complement screening (CH50, C4 and C3) on 25 cases, with follow-up period of 5-22 y. The results of EM revealed 17 cases (42 per cent.) of Type I and 23 cases (58 per cent.) of Type II MCGN but only 52 per cent. of Type II cases were correctly identified by light microscopy. Epimembranous deposits wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
1
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 21 publications
4
29
1
1
Order By: Relevance
“…The more probable outcome is chronic deterioration of renal function leading to ESRD in approximately half of patients within 10 yr of diagnosis (22)(23)(24)(25). In some patients, rapid fluctuations in proteinuria occur with episodes of acute renal deterioration in the absence of obvious triggering events; in others, the disease remains stable for years despite persistent proteinuria.…”
Section: Clinical Diagnosismentioning
confidence: 99%
“…The more probable outcome is chronic deterioration of renal function leading to ESRD in approximately half of patients within 10 yr of diagnosis (22)(23)(24)(25). In some patients, rapid fluctuations in proteinuria occur with episodes of acute renal deterioration in the absence of obvious triggering events; in others, the disease remains stable for years despite persistent proteinuria.…”
Section: Clinical Diagnosismentioning
confidence: 99%
“…The disease has a Caucasian racial predominance and is most commonly seen in children and adolescents (5,6). Its natural history is variable, but approximately 50% of patients progress to ESRD within 8 to 10 yr (6,7). Animal and human studies indicate that the pathophysiologic basis of DDD is an uncontrolled systemic activation of the alternative complement pathway because of the presence of an autoantibody to C3 convertase, mutations in the factor H gene, or the presence of an autoantibody to factor H (4).…”
mentioning
confidence: 99%
“…Although several studies of DDD were performed before 1990 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14), there has been only a single study in recent years evaluating the clinical characteristics and course of the disease (15). Particularly little is known about the course in adults, and only one study published in 1983 compared the features of DDD in children and adults (6).…”
mentioning
confidence: 99%
“…But, these drugs are associated with various complications and ultimately progress to end stage renal disease 6 . MPGN is a rare variety of childhood nephrotic syndrome, which accounts 5-14% on renal biopsy series and its modalities of treatment and prognosis is also guarded 7,8 . Various studies showed that 52-90% patients developed end stage renal disease (ESRD) within 10-20 years 8 .…”
Section: Introductionmentioning
confidence: 99%
“…MPGN is a rare variety of childhood nephrotic syndrome, which accounts 5-14% on renal biopsy series and its modalities of treatment and prognosis is also guarded 7,8 . Various studies showed that 52-90% patients developed end stage renal disease (ESRD) within 10-20 years 8 . In 2011, the authors managed three cases of MPGN in the Department of Paediatric Nephrology, BSMMU with injection methyl prednisolone, oral cyclophosphamide along with oral prednisolone.…”
Section: Introductionmentioning
confidence: 99%